Understanding the State of Nursing Homes and Residential Care Facilities - A Use Case to Support the Development of the Curated Data Enterprise - Shipp, Stephanie; Zhang, Stephanie; Salvo, Joseph (University of Virginia, 2022)
Use Cases are a mechanism to engage the research community and promote methodological research to develop and implement the proposed U.S. Census Bureau Curated Data Enterprise (CDE). The CDE is both an infrastructure and a continuously evolving ambition to create statistical data products that address today’s complex social problems by leveraging diverse data flows, including administrative and government records, surveys, social media, and sensors. The CDE supports discovering and integrating administrative records with survey data to study critical issues for the nation’s communities. All sources, survey and administrative, have limitations. Thus, integrating these data combines the strengths of these various sources, which allows for creating a better product to address today’s problems. This requires research on the viability of such records, record linkage technologies, and measures of uncertainty, leading to more accurate statistics about America’s people, places, and economy. This report presents a use case that could be used to develop the CDE. Examining an integrated view of nursing home and residential care facilities data requires three perspectives – residents and their families, workers, and owners. The impacts of crisis events, such as emergency preparedness response to the COVID-19 pandemic or weather or climate-related occurrences, have highlighted the need for an integrated view of nursing home and residential care for older populations. The importance of this issue is highlighted by The White House (2022) initiative for “Protecting Seniors by Improving Safety and Quality of Care in the Nation’s Nursing Homes.” Data about nursing homes and residential care facilities are abundant, but they are not well connected. The challenges in using these data sources are the different time periods, geographies, and units of analysis. Yet if integrated, they could provide a complete picture of nursing homes and residential care facilities. Potential data sources are from the US Census Bureau, Bureau of Labor Statistics (BLS), Centers for Medicare and Medicaid Services (CMS), Centers for Disease Control and Prevention (CDC), Agency for Healthcare Research and Quality (AHRQ), and non-profit enterprises, such as the Kaiser Foundation. We are missing clues for integrating these components to support the improvement of operations and the development of policies related to residential care for older populations. A new perspective is needed to join these components through the lens of existing data, addressing data challenges and gaps, partnerships, and the benefits of bringing these data together in a unified CDE. The technical challenge will be calibrating and bringing together data from federal and state agencies, foundations, and associations. Integrating Census Bureau data is the first step toward creating an integrated data-driven product. Merging these data with other Federal statistical and administrative data and data sources from nonprofit organizations and the private sector would result in a complete product.
This report was funded by U.S. Census Bureau Agreement No. 01-21-MOU-06.
Original submission date: 2024-02-15T18:24:08Z